What Kind of Theory Should Theory on Education for Human Flourishing Be?. Issue 1 (2nd January 2019) - Wolbert, Lynne S.; De Ruyter, Doret J.; Schinkel, Anders
ABSTRACT: In this article we defend the claim that theory on education for flourishing should also include nonideal theory. We observe that recent theory on education for flourishing takes the ideal of flourishing as a starting and central point of the theory, and should be seen as ideal theory. While this serves a purpose, the practical value of ideal theory is limited. In order to have a greater bearing on, and relevance for educational practice, nonideal theorizing should be encouraged.